Dielectric charging induced drift in micro device reliability-a review. (November 2016) - Zhou, Wu; He, Jiangbo; He, Xiaoping; Yu, Huijun; Peng, Bei
Abstract: The movement or migration of charges in dielectric materials like silicon oxide, silicon nitride and glass, is recognized as one of the most significant causes of drift instability of MEMS devices which utilize electrostatic capacitive methods for sensing and driving. This paper reviews the current researches on the characteristics of drift phenomenon of three micro capacitive devices, micro switches, micro resonators and micro mirrors. The dielectric charging forms including polarization, ion injection and charge migration are presented in detail to explain the process and mechanism of how the charging effects gives rise to the drift of performance and influence the reliability of micro systems, and then the corresponding solutions to overcome specific drift issues are proposed based on the essential conditions needed to cause dielectric charging.